Plagioporus wataugaensis n. sp. (Digenea: Opecoelidae) infecting intestine of northern hogsucker, Hypentelium nigricans, and white sucker, Catostomus commersonii, (Cypriniformes: Catostomidae) from the eastern USA, including an emended diagnosis, key to Nearctic congeners, and phylogenetic analysis. (August 2022) - Truong, Triet N.; Curran, Stephen S.; Reyda, Florian B.; Rash, Jacob M.; Bullard, Stephen A.
Abstract: We describe a new species of Plagioporus Stafford, 1904 infecting the intestine of two catostomids in the eastern USA. We emend Plagioporus to account for Nearctic congeners having ceca terminating at the level of the testes (previously diagnosed as having ceca terminating in the post-testicular space only) and testes in the posterior body extremity (a feature not previously considered as having generic importance). Of the accepted Nearctic species, Plagioporus wataugaensis n. sp. resembles Plagioporus serotinus Stafford, 1904, Plagioporus hypentelii Hendrix, 1973, and Plagioporus hageli Fayton and Andres, 2016 but differs from them by the distribution of the vitellarium and proportional length and relative extent of the excretory vesicle. Plagioporus wataugaensis has vitelline fields that are discontinuous at the level of the ventral sucker (vs. continuous in P. serotinus and P. hypentelii ) and follicles that surround the ceca (vs. wholly ventral to the ceca in P . hageli ) and that span the midline dorsal to the testes (vs. slightly overlapping the lateral margins of the testes). The excretory vesicle of P. wataugaensis is wholly post-testicular and short (6–9% of the body length) (vs. reaching the level of the posterior testis, 14–24% of the body length). Phylogenetic analyses of the 28S, ITS1, 5.8S, and ITS2 rDNA recovered P. wataugaensis sister to Plagioporus sinitsini Mueller, 1934. A key to the Nearctic Plagioporus spp. is provided. We regard Plagioporus shawi (McIntosh, 1939) Margolis, 1970, Plagioporus serratus Miller, 1940, and Plagioporus loboides (Curran, Overstreet, and Tkach, 2007) Fayton and Andres, 2016 as incertae sedis .